English Arabic Language Contact Phenomena In Social Media As Communicative Learning - Ahmad Saifulloh; Ardiati Lutfiatul Naziroh (Ijaz Arabi Journal of Arabic Learning, 2023)
The issue of contact meaning in communicative learning has received considerable critical attention. Translation and contact meaning are two terms that have enjoyed interpretation in modern language studies. Translation has enternaly been considered a bridge that connects languages and introduces readers to new cultures and knowladge. Translation is a very tricky task of linguistics (Pym,2023). Contact meaning is required for understanding translation, Language contact is the social and linguistic phenomenon by which speakers of different languages (or different dialects of the same language) interact with one another, leading to a transfer of linguistic features (Rodríguez,2019). Language contact is not, of course, a homogeneous phenomenon.